2018
DOI: 10.3390/catal8040160
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activities of Noble Metal Phosphides for Hydrogenation and Hydrodesulfurization Reactions

Abstract: In this work, the development of a highly active noble metal phosphide (NM X P Y)-based hydrodesulfurization (HDS) catalyst with a high hydrogenating ability for heavy oils was studied. NM X P Y catalysts were obtained by reduction of Padded noble metals (NM-P, NM: Rh, Pd, Ru) supported on SiO 2. The order of activities for the hydrogenation of biphenyl was Rh-P > NiMoS > Pd-P > Ru-P. This order was almost the same as that of the catalytic activities for the HDS of dibenzothiophene. In the HDS of 4,6-dimethyld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
(54 reference statements)
0
10
0
1
Order By: Relevance
“…Transition metal phosphides (TMPs, TM = Fe, Co, Ni, Mo, W, and Cu), which were widely applied in various hydrotreating processes, such as hydrodesulfurization, hydrodeoxygenation, and hydrodenitrogenation, have recently gained considerable interest as potential catalysts for HER. The pioneering research by Paseka , and Burchardt demonstrated that amorphous transition metal (e.g., Ni, Co, and Fe) phosphorus “alloys” are electrocatalytically active in promoting the HER at relatively high overpotentials in alkaline media. In 2005, inspired by the HER catalytic activity of [NiFe] hydrogenase, Liu and Rodriguez predicted that Ni 2 P­(001) could be an excellent catalytic surface toward HER, even better than the benchmarking Pt-group catalyst.…”
Section: Non-noble-metal-compound-based Her Electrocatalystsmentioning
confidence: 99%
“…Transition metal phosphides (TMPs, TM = Fe, Co, Ni, Mo, W, and Cu), which were widely applied in various hydrotreating processes, such as hydrodesulfurization, hydrodeoxygenation, and hydrodenitrogenation, have recently gained considerable interest as potential catalysts for HER. The pioneering research by Paseka , and Burchardt demonstrated that amorphous transition metal (e.g., Ni, Co, and Fe) phosphorus “alloys” are electrocatalytically active in promoting the HER at relatively high overpotentials in alkaline media. In 2005, inspired by the HER catalytic activity of [NiFe] hydrogenase, Liu and Rodriguez predicted that Ni 2 P­(001) could be an excellent catalytic surface toward HER, even better than the benchmarking Pt-group catalyst.…”
Section: Non-noble-metal-compound-based Her Electrocatalystsmentioning
confidence: 99%
“…As an important class of catalytic materials, metal phosphides hold great potential in many thermal catalytic (e.g., hydrogenation, hydrodesulfurization, and hydrodenitrogenation reactions) and electrocatalytic (e.g., hydrogen evolution reaction (HER), oxygen reduction reaction (ORR) and oxygen evolution reaction (OER)) reactions. , Many previous studies point out that bimetallic materials exhibit more excellent catalytic activities than the monometallic ones, especially for the OER. ,, However, an accurate search for optimal bimetallic or multimetallic phosphide candidates for a specific catalytic reaction has been obstructed by the lack of synthetic strategy that can isolate the composition effect from others variables (size, shape, crystal phase, etc.). Using the OER as a model reaction, we demonstrate that the programmable synthesis of CoMP x NRs with highly consistent 1-D morphology and structure can provide an unprecedented opportunity to rapidly screen the multicomponent composition effect.…”
Section: Resultsmentioning
confidence: 99%
“…Metal phosphides are a recent development in highly active HDS catalysts 9) -22) . We reported that rhodium phosphide (Rh2P) supported on silica (SiO2) showed higher activities for hydrogenation of biphenyl and HDS of 4,6-dimethyldibenzothiophene than sulfided NiMo/Al2O3 and other noble metal phosphide catalysts 22) . High HDS activity of the Rh2P catalyst will depend on the high hydrogenation activity for aromatic compounds 22) and sulfur tolerance 18),22) .…”
Section: Introductionmentioning
confidence: 99%